2019
DOI: 10.1302/1863-2548.13.190053
|View full text |Cite
|
Sign up to set email alerts
|

An electronic patient-reported outcomes measurement system in paediatric orthopaedics

Abstract: Purpose The purpose of the study was to evaluate the reliability, review differences and assess patient satisfaction of electronic patient-reported outcome measures (PROMs) compared with paper PROMs. Methods Participants between 12 and 19 years of age with a knee-related primary complaint were randomized into two groups. Group 1 completed paper PROMs followed by electronic, while Group 2 received the electronic followed by paper. PROMs included the Pediatric International Knee Documentation Committee (Pedi-IKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…12 Such objective scores and patient-reported outcome measures continue to efficiently measure the quality of healthcare provided to patients. 22…”
Section: Discussionmentioning
confidence: 99%
“…12 Such objective scores and patient-reported outcome measures continue to efficiently measure the quality of healthcare provided to patients. 22…”
Section: Discussionmentioning
confidence: 99%
“…[8,11] In previous studies, the HSS Pedi-FABS has shown to capture changes in physical activity due to recent injury more likely than the Marx Activity Scale, to have more correlations with an athlete's participation in sports than the Tegner activity scale and to be reliable as patient reported outcome measure (PROM) captured electronically as on paper. [29,30,31] This study had certain limitations. Criterion validity could not be assessed, as there was no "gold standard" for questionnaires on physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…14,24 Likewise, the HSS Pedi-FABS shows high agreement between paper and electronic versions when using Oberd in this patient population. 27…”
Section: Methodsmentioning
confidence: 99%